(untitled) (Annals of Medical Research, 2021)
Aim: Delirium is a serious complication seen postoperatively in patients undergoing cardiovascular surgery. In this study, we aimed to investigate the effect of midazolam given preoperatively on the incidence of delirium in the postoperative period in patients undergoing open heart surgery. Material and Methods: The files of patients who underwent open heart surgery between 2017-2019 in Cardiovascular Surgery Intensive Care Unit were retrospectively reviewed. 50 patients were included in the study. Ramsey Agitation Sedation Scale (RASS) and Confusion Assessment Method (CAM-ICU) values were recorded preoperatively, before and after extubation, in the ICU (after the first 24 hours) and after service transfers. Patients were divided into two groups as midazolam used or midazolam-free.Results: 28 patients were male (56%) and 22 were female (44%). The rate of delirium before extubation (T0) during the ICU stay period was significantly higher in the group without midazolam (p = 0.01). Similarly, the rate of delirium after extubation (T1) was found to be high in the group without midazolam (p = 0.00). There were also significant differences in extubation times. It was found 5.48 ± 1.08 hours in the group using midazolam and 8.3 ± 0.69 hours in the group without midazolam (p = 0.00).Conclusion: The use of midazolam in induction and perfusion in patients undergoing cardiopulmonary bypass could reduce the development of delirium in the postoperative period. Besides, RASS and CAM-ICU evaluation forms could be useful in early detection and monitoring of postoperative delirium.